Development and validation of Malaysian one stop crisis center service quality instrument (OSCC-Qual) for domestic violence management - Chew, Keng Sheng; Shirly Wong, Siew Ling; Siew, Ke Lin; Vanitha, Kandasamy (Springer-Nature, 2024)
One Stop Crisis Center (OSCC) is a multi-sectorial center aimed to provide medical, social, legal, police and shelter services to survivors of domestic violence, rape, sexual assault, sodomy and child abuse. Although OSCCs have been established\ for almost three decades in different parts of the world including in Malaysia, there is a lack of a validated instrument to measure the service quality rendered in OSCCs. A validated instrument known as OSCC-Qual was developed using a 5 stage approach where (1) in stage 1, group discussions were conducted among all authors to identify potential items for the instrument; (2) in stage 2, content validation was performed by 13 experts using content validity index and modified kappa; (3) in stage 3, exploratory factor analysis was performed by 141 healthcare staff with experience in managing OSCC cases to validate the items as well as to identify the number of factors in the instrument; (4) in stage 4, confirmatory factor analysis was performed by 110 domestic violence survivors to ascertain the validity of the factors and items retained in stage 3 and (5) in stage 5, forward and backward translation into local Malay and Chinese languages was performed. Results: In stage 1, a total of 42 items were identified. No item was deleted in stage 2. In stage 3, a total of 7 factors (i.e., “information provision”, “competency of staff”, “professionalism”, “supportive environment”, “attitude of staff”, “multi sectorial coordination” and “tangibles”) were identified. Four items were deleted due to poor factor loading. In stage 4, another 3 items were iteratively removed due to poor factor loading. Discriminant validity was good. Conclusion: With the availability of the 7-factor and 35-item OSCC-Qual instrument, it is hoped that the efficiency of OSCC in achieving its philosophical objectives after three decades of implementation can be unraveled and remedial actions can be taken, if necessary.